The Study of the Compressibility Characteristics of Soft Soil in Sarawak - Wong Seak, Yeo (Universiti Malaysia Sarawak, UNIMAS, 2005)
The present study investigates the compressibility characteristics of soft soil in Sarawak. To accomplish this study, eight undisturbed soil samples are collected from different location i.e., Desa Senadin (Miri), Kampung Punang (Lawas), Lundu (Kuching), Dan (Mukah), Sungai Miri (Miri) and Upper Lanang (Batang Rajang). Different laboratory tests (moisture content, Atterberg limit, specific gravity, grain size analysis, and consolidation) have been conducted on these soil samples. The results reveal that the value of co-efficient of volume change, mv for all the soil samples is gradually decreasing with the increase of higher-pressure ranges but the co-efficient of consolidation, cv for all the samples tested do not follow any specific trend with the increase of pressure. The compression index, Cc values calculated from e-log P graph and formula ( Cc = 0.009 × (wL-10) ) are correlated with the values of plasticity index (PI).